ChemInform Abstract: The New Misfit Compound (BiSe)1.15(TiSe2)2 and the Role of Dimensionality in the Cux(BiSe)1+δ(TiSe2)n Series. Issue 7 (18th February 2014) - Trump, Benjamin A.; Livi, Kenneth J. T.; McQueen, Tyrel M.
Abstract Single crystals of (BiSe)1.15(TiSe2)2 and (BiSe)1.13(TiSe2) are prepared from Bi, Ti, and Se in the molar ratio1:1:3 by vapor transport with TeCl4 as transport agent (750—680 °C, 7 d).